The Influence of STEAM Education on Students' Interest in Technology at Middle Schools in Indonesia - Huda, Nuril; Fransiska, Fini Widya; Mokodenseho, Sabil; Tabilantang, Boby Hidayat; Mokodompit, Ayudia (Eastasouth Institute, 2024)
This research investigates the impact of STEAM (Science, Technology, Engineering, Arts, and Mathematics) education on student interest and technology integration in Indonesian secondary schools through a quantitative analysis. A sample of 250 students was surveyed, and data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results reveal significant relationships between STEAM education, student interest, and technology integration. The measurement model demonstrates robust reliability and validity, while discriminant validity is supported. The structural model indicates that STEAM education positively influences both student interest and technology integration, with student interest mediating the relationship between STEAM education and technology. The study provides practical implications for educational practices, emphasizing the importance of transdisciplinary collaboration and effective teaching strategies to enhance student interest and foster technology integration in secondary education.